The Effectiveness of Introduction, Connection, Application, Reflection, and Extension Learning Model Based on PhET Simulation in Improving Students' Cognitive Ability on Dynamic Fluid Material - Putri, Mega Amalia; Sinaga, Parlindungan; Imansyah, Harun (Berkala Ilmiah Pendidikan Fisika, 2024)
This research aimed to assess the enhancement and effectiveness of the ICARE instructional approach, utilising PhET simulations, in augmenting students' cognitive abilities. The study employed a quantitative quasi-experimental design utilising a non-equivalent control group design. The sampling technique in this study was Convenience sampling involving 68 grade XI students (32 experimental class students and 36 control class students) in one of the public high schools in Bandung City. Student cognitive data was collected using a multiple-choice test instrument consisting of 23 questions designed by the researchers. Data analysis was employed to assess the improvement of cognitive ability through N-Gain calculation. In addition, statistical tests and effect size were used to evaluate the effectiveness of the ICARE learning model based on PhET simulation. The findings indicated that the group implementing the ICARE learning model based on PhET simulation demonstrated a greater cognitive ability enhancement than the group solely utilising the ICARE learning model. Statistical analyses revealed a significant disparity in cognitive ability improvement between students utilising the PhET-based ICARE learning model and those solely employing the ICARE learning model. Furthermore, effect size calculations indicated a notable discrepancy in cognitive ability enhancement between the experimental and control groups, characterised by a high category distinction. Therefore, it can be concluded that research using the ICARE learning model based on PhET simulation effectively improves students' cognitive abilities on dynamic fluid material.